AMPHIBIAN AND ICHTHYOFAUNAL RICHNESS AND HYDROBIOLOGICAL PARAMETERS OF PONDS AND RESERVOIRS IN GAYA, INDIA - KUMAR, PAWAN; PANKAJ, NALINAKSH (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
Background: Reservoirs and ponds are an important habitat to develop a number of species related to fishes and amphibians. Physico-chemical parameters as well as seasonal variations influence the presence of such species. A survey to determine many fish and amphibian species was conducted. The results were quiet fluctuating. Reason of this kind of variations is quality of water, habitat and seasonsal variation. It was based on a statistical analysis. Materials and Methods: An investigation of fish species as well as amphibian richnes was conducted from June’ 2018 to May’ 2019. The survey was done in five major ponds of Gaya city, India; Which was in and around (i) Suryapokhra (ii) Digghi (iii) Ramsagar (iv) Vaitarni and (v) Rukmini Pond. The study was continued with presence of particular species in relation to physico-chemical characteristics of pond. Samples of fishes were collected by fish farmers and put into water for identification. Amphibian species were photographed during day and night hours. Sampling was done during pre-monsoon, monsoon and post-monsoon periods. A total of 46 fish species belonging to 8 orders and 19 families and 12 Amphibian species belonging to 8 genera of 4 families were recorded. For physico-chemical characteristics, water samples was collected on monthly basis. Water depths of pond were measured by secchi disc. Dissolved Oxygen estimation was done by using Winkler’s method. Carbonate and Bicarbonate availability was estimated in the laboratory using volumetric analysis. Simpson Diversity Index and regression analysis were done to show the species richness and their relation with hydrobiological parameters. Results and Conclusion: A wide fluctuation of physico-chemical characteristics was observed which determines the presence of particular fish and amphibian species. Some ponds like Ramsagar and Digghi bear a green vegetation around the pond, which provide habitation and survival of amphibian species. However DO is reported to be less in these ponds (Ramsagar and Digghi). Ponds like Suryapokhra and Viatarni have respectable concentration of DO and pH which are good for development of fish species. A total of 46 fish species and 12 amphibian species were identified. The data were analysed by statistical analysis using Simpson Diversity Index and regression method.